Comparative study of two histopathological classifications for oral squamous cell carcinoma - Bruna Cristina Longo; Emylle Caroline B. F. Pereira; Débora Cecília N. Rossi; Leonardo S. Pereira; Ricardo D. Coletta; Carlos F. Morais; Iris S. Calone
ABSTRACT Introduction: Squamous cell carcinoma (SCC) is the most common tumor among all cancers in the oral cavity. Despite advances, the prognosis of this neoplasm remains a challenge for professionals. Faced with this situation, several studies try to associate the histopathological analysis with prognosis, so that therapeutic planning becomes more accurate. Objectives: This research aimed to conduct an epidemiological study of oral SCC and classify them histopathological assessment according to the World Health Organization (WHO) and the Budding and Depth of Invasion (BD) model. A retrospective research was conducted. Methodology: Data from medical records filed at UOPECCAN Hospital between 2009 and 2015 were analyzed. The sample consisted of 57 patients. Epidemiological data were collected and the blocks were rescued and cut for histopathological analysis. Associations were performed using the chi-square test with a significance level of 5% (p = 0.05) by the GraphPad Prism program. The two histopathological analyzes were correlated using Spearman's statistical test. Results: After analyzing the samples, we found a higher prevalence of oral SCC in male smokers aged above 40 years. There was no correlation between the BD and WHO methods. The WHO classification was significantly associated with age (p = 0.03), and follow-up care (p = 0.05). However, the BD model associated lymph node involvement (p = 0.005) and clinical staging (p = 0.005). Conclusion: The BD classification was more objective for histopathological analysis and may be an important tool for analyzing patient prognosis, assisting in the treatment decision.